Academic Stress and Emotional Well-Being in United States College Students Following Onset of the COVID-19 Pandemic - Clabaugh, Alison; Duque, Juan F.; Fields, Logan J. (Frontiers in Psychology, 2021)
COVID-19 has resulted in extraordinary disruptions to the higher education landscape. Here, we provide a brief report on 295 students’ academic perceptions and emotional well-being in late May of 2020. Students reported high levels of uncertainty regarding their academic futures as well as significant levels of stress and difficulty coping. These outcomes were related to higher levels of neuroticism and an external locus of control. Female students reported worse emotional well-being compared to males, and students of color reported significantly higher levels of stress and uncertainty regarding their academic futures compared to White students. These results suggest that some students may be at particular risk for academic stress and poor emotional well-being due to the pandemic and highlight the urgent need for intervention and prevention strategies.